2014
DOI: 10.1007/s10067-014-2662-7
|View full text |Cite
|
Sign up to set email alerts
|

An update on the contribution of the MHC to as susceptibility

Abstract: The 40-year-old association of HLA-B27 with ankylosing spondylitis is one of the best examples of disease association with a hereditary marker. Genomewide association and family studies suggest that other important major histocompatibility complex (MHC) influences are operative in ankylosing spondylitis (AS) susceptibility. HLA-B27 positive hepatitis C individuals are immunologically more efficient in combating viral infections such as HIV-1, hepatitis C, and influenza and less efficient in combating against c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 44 publications
(53 reference statements)
0
28
1
1
Order By: Relevance
“…Ankylosing Spondylitis (AS) is an autoimmune disease, which is characterized by involving the axial joint and ligament and tendon adhesion of inflammatory changes . Since it is subject to genetic and environment factors, the pathogenesis of AS is very complex . Recent studies have demonstrated that NK cells are generally considered to play important roles in the process of cell killing and are associated with the pathogenesis of AS .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ankylosing Spondylitis (AS) is an autoimmune disease, which is characterized by involving the axial joint and ligament and tendon adhesion of inflammatory changes . Since it is subject to genetic and environment factors, the pathogenesis of AS is very complex . Recent studies have demonstrated that NK cells are generally considered to play important roles in the process of cell killing and are associated with the pathogenesis of AS .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Since it is subject to genetic and environment factors, the pathogenesis of AS is very complex. 3,4 Recent studies have demonstrated that NK cells are generally considered to play important roles in the process of cell killing and are associated with the pathogenesis of AS. 5,6 Isobaric tags for relative and absolute quantitation (ITRAQ) is widely used for generating quantitative proteomic expression profi les and is regarded as a powerful new tool for proteomic research in many autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…One of the eight was confirmed as HLA‐B27 negative by the molecular typing method, resulting in one false positive outcome on the BD FACSVia system. Four “Inconclusive” determinations reported on the BD FACSVia system [and negative or positive on the BD FACSCalibur] were confirmed by the molecular typing method as either HLA‐B27 negative or positive, matching the BD FACSCalibur determinations. None of the HLA‐B27 positive samples determined by the molecular typing method was identified as negative by either system.…”
Section: Discussionmentioning
confidence: 61%
“…HLA‐B27 is a class I antigen molecule of the major histocompatibility complex. It is well documented that HLA‐B27 is a genotype common to a number of rheumatic inflammatory disorders, such as ankylosing spondylitis (AS), Reiter's syndrome, acute anterior uveitis, as well as inflammatory bowel disease . HLA‐B27 is strongly associated with AS, a systemic inflammatory disease that affects the spine and the sacroiliac and peripheral joints.…”
Section: Introductionmentioning
confidence: 99%
“…HLA-B27 is a highly polymorphic molecule containing over 116 protein subtypes; HLA-B27:01 and B27:117 subtypes are best known. Currently, considering the antigen structure, the most similar to HLA-B27 is HLA-B40, B40:01 subtype to be more precise [6].…”
Section: Discussionmentioning
confidence: 99%